Inhibiting Effect of Macrolide Polyene Antibiotics on Reproduction of Viruses - A. A. Bagirova; I. M. Guseynova; M. F. Gafar-Zade; H. M. Kasumov (Антибиотики и Химиотерапия, 2020)
The review provides a comparative analysis of the inhibitory effect of macrocyclic polyene antibiotics on the reproductive properties of some viruses of various structures — vesicular stomatitis virus (VSV), human immunodeficiency virus (HIV), enterovirus, influenza virus, etc. The data on the morphological structure of viruses and on the mechanism of penetration of viruses into cells are presented. The article also provides data on the transcription, assembly of viruses, and inhibition of the process of virus replication in cell cultures in vitro using macrolide polyene antibiotics. On the basis of experimental data for the studied viruses, a polyene antibiotics' blocking mechanism of the process of virus penetration through cytoplasmic membranes and their reproduction in the cell is proposed.